PARTISIPASI MASYARAKAT DALAM PENGELOLAAN LINGKUNGAN LAHAN PEKARANGAN DI KELURAHAN LOKTABAT UTARA KOTA BANJARBARU - Nor Zainap; Athaillah Mursyid; yusuf Azis; Zuraida titin Mariana (EnviroScienteae, 2012)
Research on community participation in environmental management through the use of this resource is very interesting to study. This is caused by the narrowness of the courtyard area of the existing Village North Loktabat housing. The purpose of this study were: 1) Determine the level of public participation in environmental management through the use of yard area, 2) identify the relationship between community participation with social variables (education, age, occupation, and income), cultural (customary), information, counseling, long living, and home ownership status in environmental management through the use of yard area. This research was conducted by survey method. The results showed that the North Loktabat village community, whether it is located in residential areas independently (villages) and also in the complex area has a high level of participation in the management of yard area. Based on the research also shows that social and cultural variables do not have a close relationship with participation. Variables such as information, counseling, long settled and the status of home ownership have a strong relationship with participation in environmental management of their yards.